Multiscale insights into the phase-dependent sintering of Fe2O3 and Fe3O4 under chemical looping conditions - Guanshan Liu; Yang Lei; Yayong Zhang; Huijun Ge; Tao Zhang; Rui Tan; Mudi Wu; Shiwei Ma; Mingwu Tan; Tao Song (Fuel, 2027)

Impacts of speed limits on emissions, energy consumption and traffic efficiency - Shi-Teng Zheng; Junfang Tian; Rui Jiang; Bin Jia; Ying-En Ge (Transportation Research Part D: Transport and Environment, 2026)

Recycled seawater chlorine in the lithospheric mantle facilitates metal enrichment in collisional orogens - Jingbo Zhang; Rui Wang; Zoltán Zajacz; Alexandra Tsay; Adam C. Simon; Wen-Jie Xia; Yun-Zhao Ge; Zeng-Qian Hou (Earth and Planetary Science Letters, 2026)

Progressive horizon extrapolation with wavelet-based directional modeling for regional wind vector field prediction - Shidong Chen; Baoquan Zhang; Dong Liu; Xutao Li; Yunming Ye; Yangjinxi Ge; Rui Ye (Ocean Engineering, 2026)

Short-term nitric oxide gaseous treatment of post-rigor pork: Multidimensional impacts on meat quality, protein oxidation and proteolysis, and microstructure - Jiaye Zhu; Yongmao Ye; Liangyu Zhang; Haoyang Ma; Xinnuo Zhou; Yu Qi; Qingfeng Ge; Mangang Wu; Hai Yu; Rui Liu (Food Chemistry, 2026)

Phenolic acid-modified Arabic gum as an advanced functional stabilizer to enhance gelation and water retention of emulsion-type myofibrillar protein gels under oxidative stress - Tianhao Zhu; Mingze Xu; Yi Luan; Khubaib Ali; Peipei Yin; Qingling Wang; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Hydrocolloids, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Predicting public building energy consumption in the early design stage using a multi-agent LLM for occupant behavior simulation - Rui Dai; Guoqiang Zhang; Linhu Wang; Liuchang Yang; Ge Bai (Building and Environment, 2026)

A cross-city assessment method for street greenery equity based on the green landscape index - Jiayu Ge; Hao Chen; Xiaoping Rui; Yingxing Chen; Yiying Liu; Yunqiang Zhu (Urban Ecosystems, 2026)

Microplastic pollution in an anthropogenically modified river: sediment occurrence, associated microbiota, and environmental correlates - Kai Zhang; Ge Ma; Qingyi Wang; Chengshi Ding; Xinlu Shen; Chaoyue Zhao; Siwei Gao; Chenyang Shen; Hui Gao; Rui Xin; Fengxia Yang (Environmental Monitoring and Assessment, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Design-stage prediction of building energy consumption with occupant behavior using a human-in-the-loop transformer - Rui Dai; Guoqiang Zhang; Ge Bai; Liuchang Yang; Minghao Wang; Zujun Wang (Energy and Buildings, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Evaluation of microplastic removal performance and technologies in secondary effluent from typical sewage treatment processes using a self-developed enrichment–purification–separation-integrated device - Wenjuan Zhang; Xin Zhang; Li Fan; Siyu Wang; Shuang Ge; Rui Miao; Lei Wang; Yongtao Lv (Process Safety and Environmental Protection, 2026)

Dendrobium officinale leaf extract extends the mean lifespan in Caenorhabditis elegans via the DAF-16/SOD-3 axis - Cheng Gong; Shu Feng; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Shikuan Zhao; Rui Zhou; Li Feng; Yunfei Ge; Ruijuan Yang; Chongye Fang; Xiaocui Du (Biogerontology, 2026)

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

An AI-driven MABM–BIM–DL framework for energy consumption prediction in three representative types of urban public buildings in Wuhan - Rui Dai; Guoqiang Zhang; Shengbiao Li; Ruiying Zhang; Ge Bai (Sustainable Cities and Society, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

Distributed nonlinear placement problems in the NASVs with nonsmooth objectives and unknown time-varying actuator faults - Wen-Jin Liu; Rui-Qi Cao; Xinxin Zhang; Xiang-Yu Yao; Ming-Feng Ge (Ocean Engineering, 2026)

Corrigendum to “Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems” [Food Res. Int. 235 (2026) 119173] - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Numerical manifold method for compression molding of granular materials - Xuezhen Zhai; Yuchen Guo; Yongjia Zhang; Rui Yue; Liuchen Shu; Youjun Ning; Pengwan Chen; Ge Kang (Computers and Geotechnics, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Synergistic catalytic co-liquefaction of lignin and polyethylene in a water–pentane biphasic system: An efficient route to sustainable liquid fuels - Shitong Yu; Zhitong Ge; Samudrala Shanthi Priya; Kuen Kee Hyun; Saidakmalov Saidalo; Khusenov Arslonnazar; Samir I. Gadow; Jun Xiao; Rui Xiao; Zhicheng Luo (Waste Management, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Impact Mechanical Behavior and Energy Dissipation Analysis of Rock-Concrete Composites with different Interface Roughness - Wei-jing Yao; Han-bing Xu; Sheng-qi Yang; Shao-ge Rui; Jian-yong Pang (Applied Geophysics, 2026)

Dynamic recovery sequence optimization of subway-bus network with constrained reinforcement learning - Shan Liu; Zhenhao Meng; Rui Jiang; Zhengli Wang; Ya Zhang; Ying-En Ge (Transportation Research Part D: Transport and Environment, 2026)

Sustained grain cadmium reduction in rice-wheat rotation: A cost-effective CaCO3-based amendment strategy from three-year trials - Zhi-Xian Tang; Ge Dong; Zhong-Rui Xu; Zhong Tang; Fang-Jie Zhao; Peng Wang (Journal of Environmental Management, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Fabrication and physicochemical characterization of SPI-gallic acid-guar gum ternary complexes: Insights into covalent bonding and structural tunability - Mingze Xu; Chen Gu; Khubaib Ali; Peipei Yin; Chang Liu; Rui Sun; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Chemistry, 2026)

Chemically modified bacterial cellulose–mediated fiber salting-out method for preparing tough hydrogels - Bei Zhang; Xin-Xin Chen; Xiao-Rui Ge; Xin-Ping Wang; Xiao-Hui Yao; Wei-Guo Zhao; Tao Chen; Dong-Yang Zhang (Carbohydrate Polymers, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

YOLO-FR: An enhanced object detector for small object detection in complex scenes - Rui Fan; Renhao Jiao; Weigui Nan; Jin Dang; Zhixue Wang; Xuefeng Ge; Baiying Dong; Xiaoli Luo (Remote Sensing Applications: Society and Environment, 2026)

Numerical prediction on cavitation characteristics of a marine propeller in oblique flow without and with hull wake effects - Yu Sun; Shengyao Ge; Rui Wu; Wenyu Chen; Han Han; Depeng Ma; Huan Ping (Ocean Engineering, 2026)

Effects of ibuprofen and its transformation products on algal-bacterial granular sludge system - Jingxin Nie; Rui Ouyang; Hongmei Ge; Lu Cai; Shulian Wang (Journal of Environmental Management, 2026)

The role of co-ion transport in selectrodialysis for mono/divalent cation separation - Xixi Ma; Qian Chen; Lanlan Zhang; Shanshan Liu; Zixuan Wu; Rui Li; Zhiguo Dong; Weiwei Li; Jinfeng He; Chuanrun Li; Liang Ge; Haiyang Yan (Desalination, 2026)

Tracking the fate of organophosphate esters: from occurrence to risk in the lower Yangtze River water - Yi Zhou; Wenxuan Ma; Wanyu Li; Ge Yin; Jiajun Chang; Yao Xiao; Zhiliang Zhu; Rui Wang; Yanling Qiu (Environmental Science and Pollution Research, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Bio-diesel quality characterization towards bio-jet fuel production using infrared spectroscopy and an interpretable machine learning framework - Chao Chen; Rui Liang; Yadong Ge; Ruodong Wang; Yanhui Men; Junyu Tao; Beibei Yan; Zhanjun Cheng; Xuebin Lv; Guanyi Chen (Journal of Environmental Management, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Revised modality-driven approach for enhanced analytical solutions to complex multi-mode coupled flutter: Influence of suspension bridge configurations - Jinbo Zhu; Yongxin Yang; Jinjie Zhang; Haojun Xu; Yaojun Ge; Rui Zhou; Yunliang Shi; Aihong Kang (Engineering Structures, 2026)

Robust oxygen vacancy surfaces induce chemical bonding interfaces of Bi2Sn2O7/Bi2MoO6 S-scheme heterojunction with asymmetric adsorption sites for efficient photocatalytic nitrogen fixation - Yongli Li; Xin Kong; Rui Bao; Liang Liu; Zhenhua Ge; Feng Liu; Hao Cui; Jianhong Yi (Chemical Engineering Journal, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

An approach for formulating dynamic irrigation schedules in alfalfa based on virtual-real fusion - Yongqi Ge; Rui Liu; Pengpeng Sun; Liguo Dong; Libo Liu (Plant and Soil, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

Perspectives on the role of postbiotics in meat and meat products: Current status and future trends - Du-xin Jin; Gui-peng Zou; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Meat Science, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Early-life exposure to polystyrene nanoplastics at ambient doses induces neurotoxicity via mTOR-mediated autophagy-lysosomal dysfunction and proteostasis imbalance - Ge Yang; Yang Peng; Jinghan Li; Shuiqing Yang; Min Li; Xinyue Zheng; Xinyue Chen; Jian Wan; Zhihong Zhu; Ling Zhang; Rui Li (Journal of Hazardous Materials, 2026)

Towards sustainable desertification control: A manufacturing method for porosity-controlled upright reed sand fences - Manyu Jin; Yijiang Zheng; Yun Ge; Baojian Ma; Jiangyu Zhang; Rui An; Jianjun Cheng (Journal of Environmental Management, 2026)

Study on liver injury caused by lipid accumulation induced by PM2.5 through IRE1α-XBP1s pathway of endoplasmic reticulum stress in mice - Xinyue Zheng; Fei Hu; Ge Yang; Xinyue Chen; Min Li; Shuiqing Yang; Jinghan Li; Yang Peng; Ling Zhang; Jian Wan; Rui Li (Journal of Environmental Sciences, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

The correlation between social support and hopelessness among cancer survivors: a meta-analysis - Lu-Ting Shen; Jian-Zeng Lan; Attiq-Ur-Rehman; Wei Li; Meng-Wei Ge; Rui Feng; Kang Zhong; Si-qi Gao; Hong-Lin Chen (Cancer Causes & Control, 2026)

Trade and port-based resilience analysis under the expansion of the belt and road trade agreement: an integrated economic and environmental assessment - Jackson Jinhong Mi; Shaowei Rui; Hongguang Zhu; Jinfeng Ge; Xinqiang Chen (Frontiers in Marine Science, 2026)
Trade cooperation represents a fundamental and crucial element within the framework of the Belt and Road Initiative. This paper selects representative countries with Belt and Road trade agreement that are under negotiation, under study, and accessible. Employing the Global Trade Analysis Project (GTAP) model, the study simulates seven distinct scenarios for the expansion of these trade agreements, analyzes the economic benefits under different scenarios, and constructs a multi-region input–output table. A Global Trade Analysis Project-Multi Region Input Output (GTAP-MRIO) model is extended to capture carbon flows from maritime trade and port-related logistics sectors. We obtain several findings. Regarding economic benefits, the expansion of the Belt and Road trade agreement can improve China’s terms of trade, increase the scale of China’s total output and total imports, increase GDP growth, and increase social welfare. Regarding industrial output, the output of technology-intensive industries is likely to increase, and the output of energy-intensive industries is predicted to increase significantly. The transfer of carbon emissions from China to other countries is predicted to decrease, and the transfer of carbon emissions from China’s exports comes mainly from energy-intensive industries. These predictions based on model analysis offer theoretical guidance and policy recommendations for the pursuit of green and high-quality sustainable development within the framework of the Belt and Road Initiative.

Three new species of Scleroderma from Southern China - Ling Li; Hua Qu; Rong-Qian Bi; Rui Wu; Hai-Jiao Li; Zai-Wei Ge (Mycological Progress, 2026)

Remediation of ternary heavy metal-polyethylene microplastics co-contaminated soil using co-modified biochar with deep eutectic solvent and warm patch: competitive interactions, mechanistic insights, and microbial community response - Luxin Zhang; Xiaobing Liu; Sishang Ge; Weiwei Shi; Rui Zhang; Chaoyang Li; Rong Chen (Environmental Research, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

An Indirect Foot-End Touchdown Detection Method for the Underwater Hexapod Robot - Zonglin Liu; Meng Wang; Tong Ge; Rui Miao; Gangtai Lu (Journal of Marine Science and Engineering, 2025)
The underwater hexapod robot has advantages such as lower energy consumption and reduced environmental interference compared to ROVs and AUVs. The foot-end contact detection with the seabed is the key technology for adapting to complex terrains. This paper focuses on the ‘Dragon Crab’ underwater hexapod robot developed by Shanghai Jiao Tong University and proposes an indirect detection method that does not require foot-end contact sensors. By establishing the kinematic and dynamic models of the robot’s legs, combined with multi-order polynomial trajectory planning to reduce non-contact force interference, the foot-contact determination condition is defined. Through simulation experiments and force analysis of the legs, the contact detection parameters are estimated. Then, single-leg contact tests are conducted to obtain joint motor torque variation curves and foot-end height variation curves through the kinematic model, verifying the proposed contact detection conditions and parameters. Finally, the method is applied to underwater obstacle-crossing experiments of the underwater hexapod robot using triangular and wave gait patterns. Experimental results show that the method can accurately identify the foot-end contact state and has high applicability in complex underwater terrains.

Path planning and load balancing task scheduling for multi-region coverage of multi-safflower harvesting machines - Liwei Yang; Yijiang Zheng; Rui An; Xiyang Li; Yun Ge (Computers and Electronics in Agriculture, 2025)

Advancing the state of the art of cyclic direct simple shear Testing: Histories, current status, challenges and future trends - Xin Kang; Zi-Rui Ma; Louis Ge (Soil Dynamics and Earthquake Engineering, 2025)

Chitosan-derived nanoemulsion enriched with Streptomyces metabolites for target control of tobacco leaf spot, enhanced foliar retention and plant nutrition - Xue Han; Chunli Xu; Rui Yang; Dan Chen; Yaning Li; Beibei Ge (Chemical Engineering Journal, 2025)

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

Limitation of the Application of Heat Tracer in Investigating Groundwater and River Interactions under Dynamic Flow Conditions - Mengyan Ge; Rui Ma; Ziyong Sun (Journal of Earth Science, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Efficient degradation mechanism of fomesafen by earthworms and gut degrading bacteria synthetic community - Yan Ge; Aoqi Yang; Yongkang Dong; Siqi Wang; Rui Xu; Dongxing Zhou (Pesticide Biochemistry and Physiology, 2025)

Multifunctional double-layer film incorporated Pickering emulsions and polyphenol-anthocyanin co-pigmentation for maintaining and monitoring shrimp freshness - Shiqi Li; Shuo Zhang; Xuerong Hu; Jiale Zhao; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Qian Ge; Zhouli Wang (Food Research International, 2025)

Agricultural plastic Legacy in river Sediments: Abundance, oxidation, and occurrence characteristics of microplastics across rural China - Ge Ma; Kuangjia Li; Wei Zou; Rui Xin; Xiaohan Zhang; Jiaojiao Feng; Zheng Chen; Yinan Yang; Xiaomeng Lou; Kai Zhang; Fengxia Yang (Environmental Pollution, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Creep deformation characteristics and microscopic mechanism of undisturbed soils of the landslide sliding zone in the Jinpingzi area - Ruihong Wang; Rui Zhao; Ge Zhang; Bo Lu (Bulletin of Engineering Geology and the Environment, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

In situ growth of NiCo2O4 nanosheets on N,S co-doped rice husk biochar for ultrasensitive and selective Pb2 + and Cd2+ electrochemical sensing - Mingmei Ge; Xinying Han; Rui Wang; Chenxi Wu; Shiyu Wang; Bao Chang; Zhuang Miao; Yang Zhao; Huan Wang (Journal of Environmental Chemical Engineering, 2025)

A novel method for predicting debris flow hazard: a multi-strategy fusion approach based on the light gradient boosting machine framework - Tianlong Wang; Qi Ge; Tianxing Ma; Hao Chen; Rui Luo; Xu Wang; Keying Zhang; Zhaowei Chu; Xiaohui Ni; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Effects of reversing the light-dark cycle on growth performance and intestinal health in heat-stressed broilers - Huiyuan Rui; Xiangyang Xu; Fei Song; Aige Han; Meiwei Lv; Xin Kang; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Efficient Remediation of Cr(VI)-Contaminated Soil by Bismuth Sulfide Modified Euryale ferox Shell Biochar: Performance, Mechanistic Study, and Binding Energy Perspective - Xiaobing Liu; Sishang Ge; Luxin Zhang; Qunshuai Li; Zhimeng Zhao; Rui Zhang (International Journal of Environmental Research, 2025)

A hybrid estimation of distribution algorithm for agile earth observing satellite task scheduling problem - Chunchun Ma; Panxing Huang; Xiaoze Liu; Chu-ge Wu; Rui Xu (Swarm and Evolutionary Computation, 2025)

Potentially toxic elements in sediments of China's Shihe River: Urban-agricultural impact assessment and source apportionment - Kai Zhang; Ge Ma; Zheng Chen; Jilu Wang; Xiaomeng Lou; Yinan Yang; Jiaojiao Feng; Fengxia Yang; Kuangjia Li; Chenxuan Shang; Rui Xin; Xiangmin Zhang (Journal of Contaminant Hydrology, 2025)

Synthesis of high yield mesoporous silica for efficient CO2 adsorption using coal gasification fine slag - Zekai Miao; Hao Ge; Xinran Han; Rui Wu; Hai Zhu; Congchao Zhang; Shengping Wang (Fuel, 2025)

The novel MAT1-1-2 gene of golden-flower fungus from fuzhuan brick tea is required for normal colony morphology and sexual development, and affects metabolism - Jie Wang; Rui Zhang; Zhenglin Fei; Changfa Yang; Yilong Li; Yaya Yuan; Qilan Hu; Caiyan Tang; Zhonghua Liu; Mingzhi Zhu; Yongyi Ge (Food Bioscience, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

pH/GSH-Driven inside-out nanoreactor initiating copper(I)-precursor chelation-promoted bioorthogonal therapy - Zhexiang Wang; Xinyi Li; Rui Lv; Ruochen Guo; Qinglei Shu; Tianjin Ge; Jun Yan; Zhihao Zhao; Guanghui Wang; Jian Liu (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Rising temperature increases the response time of LAI and GPP to meteorological drought in China - Yufei Wang; Peng Sun; Rui Yao; Chenhao Ge (Atmospheric Research, 2025)

Global trends in staphylococcus aureus-related lower respiratory infections from 1990 to 2021: findings from the 2021 global burden of disease report - Hong Chen; Shuang Song; Rui Cui; Yong-Wang Feng; Peng Ge (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Macrofaunal biodiversity and trophic structure varied in response to changing environmental properties along the Spartina alterniflora invasion stages - Li Yang; Rui Pan; Shuang Wang; Zhangyan Zhu; Hongshan Li; Ruiping Yang; Xiaoping Sun; Baoming Ge (Marine Pollution Bulletin, 2025)

Enhancement of the flavor compound 3-Methylbutanal and sensory quality in sausages fermented by Lactococcus lactis CGMCC 31087: Leucine and α-Ketoglutaric acid as supplements - Lei Chen; Congjiao Wei; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Food Chemistry, 2025)

Permafrost thawing characterization in engineering scale by multi-geophysical methods: A case study from the Tibet Plateau - Junkai Ge; Huaifeng Sun; Rui Liu; Zhiyou Huang; Bo Tian; Lanbo Liu; Ziqiang Zheng (Engineering Geology, 2025)

Doping-engineered regulation of Co(IV)=O enhanced Fenton-like activities via electronic structure modulation on CoSCN nanotubes - Liang Ge; Jian Wei; Junyong He; Rui Sun; Wenlong Wang; Dandan Yang; Jiandong Lu; Peidong Hong; Yulian Li; Yahui Li; Chao Xie; Zijian Wu; et al. (Chemical Engineering Journal, 2025)

Superior matching between electrochemical and non-electrochemical reactions to boost furfural electro-oxidation - Jianyuan Deng; Rui Li; Kun Xiang; Longzhou Zhang; Kaihang Sun; Young Dok Kim; Zhongyi Liu; Jingmin Ge; Zhikun Peng (Chemical Engineering Journal, 2025)

Amplifying population exposure of extreme precipitation across Yellow River Basin, China at 1.5° C, 2.0° C and 3.0° C global warming - Rui Yao; Zice Ma; Peng Sun; Chenhao Ge (Natural Hazards, 2025)

Urbanization has enhanced compound heatwaves - Peng Sun; Shifang Yu; Rui Yao; Zhongbao Sun; Vijay P. Singh; Yaojin Bian; Chenhao Ge; Qiang Zhang (Journal of Geographical Sciences, 2025)

Enhanced removal of lead complexes using phosphide-modified nanoscale zero-valent iron: The boosting impact of the iron cycle - Rui Li; Xinya Liu; Xiao Ge; Xiaozhi Wang (Journal of Cleaner Production, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

A Study of a Nonsmooth Fuzzy Active Disturbance Rejection Control Algorithm for Gas Turbines in Maritime Autonomous Surface Ship - Rui Yang; Yongbao Liu; Xing He; Ge Xia; Zhimeng Liu (Journal of Marine Science and Engineering, 2025)
To address the dynamic and robust performance limitations of gas turbines in maritime autonomous surface ship applications, this paper proposes a novel nonsmooth fuzzy active disturbance rejection control (NS_FADRC) algorithm. This method combines the strengths of linear active disturbance rejection control (LADRC), nonsmooth control, and fuzzy adaptive control. First, the extended state observer (ESO) is improved by using the nonsmooth control method to enhance its convergence rate and estimation capability, while ensuring finite-time convergence characteristics. Next, fuzzy control logic is integrated to enhance the adaptability of the state error feedback (SEF), overcoming the limitations of traditional SEF in handling nonlinearities. The stability of the proposed control algorithm is further validated using Lyapunov stability analysis. Lastly, a Hardware-in-the-Loop (HIL) semi-physical simulation platform, based on automatic code generation technology, is developed to validate the algorithm’s performance. Experimental results demonstrate that, compared to the PID, FPID, and LADRC algorithms, the proposed NS_FADRC algorithm provides superior dynamic response during speed step tracking and excellent robust disturbance rejection performance in the presence of load disturbances, parameter uncertainties, and measurement noise.

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Hyperspectral image classification based on faster residual multi-branch spiking neural network - Yahui Li; Yang Liu; Rui Li; Liming Zhou; Lanxue Dang; Huiyu Mu; Qiang Ge (Computers & Geosciences, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Selenium Treatment Alleviates the Inhibition Caused by Nep-L Gene Knockdown in Silkworm (Bombyx mori) - Ting-Ting Hong; Fei Hu; Wen-Jie Ge; Rui Zhang; Juan Du; Kiran Thakur; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Computational Design and Optimization of Multi-Compound Multivesicular Liposomes for Co-Delivery of Traditional Chinese Medicine Compounds - Mengjie Rui; Yali Su; Haidan Tang; Yinfeng Li; Naying Fang; Yingying Ge; Qiuqi Feng; Chunlai Feng (AAPS PharmSciTech, 2025)

Deciphering bioprocess responses in organic phosphorus mineralization to different antibiotic stresses: Interaction mechanisms mediated by microbial succession and extracellular polymeric substances and regulatory patterns - Zhenchao Wu; Jie Kang; Liangyang Mao; Rui Sun; Xiujun Tu; Yuhao Guo; Jingping Ge (Bioresource Technology, 2025)

Drivers of ecological drought recovery: Insights from meteorological and soil drought impact - Chenhao Ge; Peng Sun; Rui Yao; Yayi Zhang; Han Shen; Huilin Yang (Journal of Hydrology, 2025)

A flexible, highly sensitive, and anti-strain interference sensing fabric based on conjugated electrospinning core–shell conductive nanofiber yarns for ultra-stable pressure sensing and human–machine interaction - Wenqi Wu; Xu Jin; Adilaimu Tiliman; Fan Zhang; Ge Bai; Yurui He; Gaoling Jin; Bin Wang; Xiuqin Zhang; Rui Wang (Chemical Engineering Journal, 2025)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Role of microglia polarization induced by glucose metabolism disorder in the cognitive impairment of mice from PM2.5 exposure - Xinyue Zheng; Fei Hu; Xinyue Chen; Ge Yang; Min Li; Yang Peng; Jinghan Li; Shuiqing Yang; Ling Zhang; Jian Wan; Nianpeng Wei; Rui Li (Science of The Total Environment, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Exploring Jiangshui-originated probiotic lactic acid bacteria as starter cultures: Functional properties and fermentation performances in pear juice - Du-xin Jin; Yu-xuan Jin; Wei Zhang; Wei Cao; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Food Bioscience, 2024)

Biosynthesis pathway of flavor compound 3-methylbutanal derived from leucine by Lactococcus lactis 517: From a transcriptomics perspective - Lei Chen; Rui Liu; Chenxiang He; Mangang Wu; Qingfeng Ge; Hai Yu (Food Bioscience, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Small-strain stiffness of compacted loess upon wetting, drying and loading: Experiments and model interpretation - Miaomiao Ge; Xiaona Han; Rui Yang; Caihui Zhu (Transportation Geotechnics, 2024)

How does the issuance of green bonds impact stock price crash risk: An analysis utilizing the NCSKEW and DUVOL - Pengfei Ge; Wen Yue; Chuxiong Tang; Rui Zhu (Journal of Environmental Management, 2024)

Constructing Ni/ZnMOx composite metal oxide adsorbents with excellent desulfurization capacity and thermal stability for reactive adsorption desulfurization - Pu Dai; Mengya Guo; Hui Ge; Caimei Fan; Xuekuan Li; Xiuquan Liu; Junpeng Feng; Rui Li; Mingxing Tang (Fuel, 2024)

Cu-substituted Na0.75Ni0.17Cu0.08Mn0.75O2 cathode with suppressing P2-O2 phase transition and air-stable for high-performance sodium-ion batteries - Guodong Hao; Shao-hua Luo; Pengyu Li; Ge Wang; Wei Zhao; Rui Huang; Haoran Zang; Jiachen Wang; Lixiong Qian (Chemical Engineering Journal, 2024)

Genome-wide association study and selective sweep analysis uncover candidate genes controlling curd branch length in cauliflower - Yingxia Yang; Yutong Guo; Jing Wang; Wenjuan Cheng; Mingjie Lyu; Qian Wang; Jianjin Wu; Mingyan Hua; Weihua Zhang; Deling Sun; Xianhong Ge; Xingwei Yao; et al. (Theoretical and Applied Genetics, 2024)

Development of a superconducting undulator cryostat based on the thermosiphon effect - Xiangzhen Zhang; Miaofu Xu; Zilin Chen; Xiangchen Yang; Tongxian Zhao; Rui Ye; Xiaochen Yang; Xiaojuan Bian; Yao Gao; Huihua Lu; Rui Ge; Zian Zhu; et al. (International Journal of Refrigeration, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

An approach for multi-depth soil moisture prediction in alfalfa based on a dual-branch combined model - Rui Liu; Lifeng Lu; Yongqi Ge; Liguo Dong; Juan Zhou (Computers and Electronics in Agriculture, 2024)

Prediction and explanation of debris flow velocity based on multi-strategy fusion Stacking ensemble learning model - Tianlong Wang; Keying Zhang; Zhenghua Liu; Tianxing Ma; Rui Luo; Hao Chen; Xu Wang; Wei Ge; Hongyue Sun (Journal of Hydrology, 2024)

Inoculation fermentation with Lactobacillus fermentum L28 and Staphylococcus epidermidis S24 for improving the protein degradation of air-dried goose - Mangang Wu; Chen Gu; Likun Duan; Peipei Yin; Tianhao Zhu; Yuyu Xu; Qing Yin; Rui Liu; Qingfeng Ge; Hai Yu (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Characteristics of propagation from meteorological drought to ecological drought in China: Lag and cumulative effects - Chenhao Ge; Peng Sun; Rui Yao; Yufei Wang; Wenhui Chen; Yaojin Bian; Qiang Zhang (Atmospheric Research, 2024)

Preparation of bacterial fertilizer from biogas residue after anaerobic co-digestion of kitchen waste and residual sludge - Chuan Li; Chang Hua; Lingling Chen; Zimei Miao; Rui Xu; Sili Peng; Zhiwei Ge; Lingfeng Mao (Environmental Science and Pollution Research, 2024)

Significant influence of urban human activities and marine input on rainwater chemistry in a coastal large city, China - Jie Zeng; Guilin Han; Qixin Wu; Rui Qu; Qing Ma; Jingwen Chen; Shijun Mao; Xin Ge; Zhong-Jun Wang; Zhiheng Ma (Water Research, 2024)

Decarbonization pathways for bulk vessels: Integrating power systems, fuels, and control measures - Yuzhe Zhao; Rui Ge; Jingmiao Zhou; Theo Notteboom (Ocean Engineering, 2024)

Are longer and more intense heatwaves more prone to extreme precipitation? - Peng Sun; Yaojin Bian; Shifang Yu; Rui Yao; Zhongtian Wang; Qiang Zhang; Wenhui Chen; Chenhao Ge; Zice Ma; Wenying Du (Global and Planetary Change, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Revealing the electrochemical-mechanical correspondence between electrode films and 20 Ah prismatic Li-ion batteries via optical fiber monitoring - Xiaoyu Ge; Yi Zhang; Rui Du; Nian Chen; Yifei Yu; Zhen Li; Yunhui Huang (Chemical Engineering Journal, 2024)

An Underwater Localization Method Based on Visual SLAM for the Near-Bottom Environment - Zonglin Liu; Meng Wang; Hanwen Hu; Tong Ge; Rui Miao (Journal of Marine Science and Engineering, 2024)
The feature matching of the near-bottom visual SLAM is influenced by underwater raised sediments, resulting in tracking loss. In this paper, the novel visual SLAM system is proposed in the underwater raised sediments environment. The underwater images are firstly classified based on the color recognition method by adding the weights of pixel location to reduce the interference of similar colors on the seabed. The improved adaptive median filter method is proposed to filter the classified images by using the mean value of the filter window border as the discriminant condition to retain the original features of the image. The filtered images are finally processed by the tracking module to obtain the trajectory of underwater vehicles and the seafloor maps. The datasets of seamount areas captured in the western Pacific Ocean are processed by the improved visual SLAM system. The keyframes, mapping points, and feature point matching pairs extracted from the improved visual SLAM system are improved by 5.2%, 11.2%, and 4.5% compared with that of the ORB-SLAM3 system, respectively. The improved visual SLAM system has the advantage of robustness to dynamic disturbances, which is of practical application in underwater vehicles operated in near-bottom areas such as seamounts and nodules.

Visualized Enzyme-Activated Fluorescence Probe for Accurately Detecting β-Gal in Living Cells and BALB/c Nude Mice - Xiaoli Huang; Le Chang; Jianxin Ge; Ping Wang; Rui Yin; Guanqi Liu; Guopin Wang (Journal of Fluorescence, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Development of a nonstationary Standardized Precipitation Evapotranspiration Index (NSPEI) and its application across China - Peng Sun; Chenhao Ge; Rui Yao; Yaojin Bian; Huilin Yang; Qiang Zhang; Chong-Yu Xu; Vijay P. Singh (Atmospheric Research, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

A review on aroma-active compounds derived from branched-chain amino acid in fermented meat products: Flavor contribution, formation pathways, and enhancement strategies - Lei Chen; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Trends in Food Science & Technology, 2024)

Ecological succession of abundant and rare subcommunities during aerobic composting in the presence of residual amoxicillin - Liangyang Mao; Jie Kang; Rui Sun; Jiaxin Liu; Jingping Ge; Wenxiang Ping (Journal of Hazardous Materials, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

GPR-TransUNet: An improved TransUNet based on self-attention mechanism for ground penetrating radar inversion - Ge Junkai; Sun Huaifeng; Shao Wei; Liu Dong; Yao Yuhong; Zhang Yi; Liu Rui; Liu Shangbin (Journal of Applied Geophysics, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Simulation and optimization of co-pyrolysis biochar using data enhanced interpretable machine learning and particle swarm algorithm - Chao Chen; Rui Liang; Junxia Wang; Yadong Ge; Junyu Tao; Beibei Yan; Guanyi Chen (Biomass and Bioenergy, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Effects of ultrasound-assisted cooking on the physicochemical properties and microstructure of pork meatballs - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Meat Science, 2024)

Improving on mapping long-term surface water with a novel framework based on the Landsat imagery series - Ling Lan; Yu-Ge Wang; Hao-Shuang Chen; Xu-Rui Gao; Xie-Kang Wang; Xu-Feng Yan (Journal of Environmental Management, 2024)

Experimental and numerical research on the failure pattern and mechanisms of granite disc with a pre-crack after heating and liquid nitrogen cooling - Yuliang Zhang; Guowei Ma; Qiang Sun; Zhenlong Ge; Xindong Wei; Zhe Li; Fuxin Rui (International Journal of Rock Mechanics and Mining Sciences, 2024)

Magnetic-encoded fluorescent nanospheres-based competitive immunoassay for near-simultaneous detection of four mycotoxins in wheat - Xueqi Lin; Rui Ge; Jie Wei; Tianhui Jiao; Qingmin Chen; Munetaka Oyama; Quansheng Chen; Xiaomei Chen (Food Chemistry, 2024)

NIR-responsive photoelectrochemical sensing platform for the simultaneous determination of tetrodotoxin and okadaic acid in Nassariidae - Chenyan Zheng; Rui Ge; Jie Wei; Tianhui Jiao; Qingmin Chen; Quansheng Chen; Xiaomei Chen (Food Chemistry, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

O2 plasma-modified carbon nanotube for sulfamethoxazole degradation via peroxymonosulfate activation: Synergism of radical and non-radical pathways boosting water decontamination and detoxification - Shiqi Liu; Zichen Zhang; Rui Lu; Yuankun Mao; Huiru Ge; Can Liu; Chenxi Tian; Siyuan Yin; Li Feng; Yongze Liu; Chao Chen; Liqiu Zhang (Chemosphere, 2023)

Synergistic effect triggered by Fe2O3 and oxygen-induced hydroxyl radical enhances formation of amino-phenolic humic-like substance - Yingchao Zhang; Zhitao Bi; Wenxin Tian; Zhenyu Ge; Yang Xu; Rui Xu; Hongqiong Zhang; Shoufeng Tang (Journal of Environmental Management, 2023)

Edible electrospun zein nanofibrous scaffolds close the gaps in biofilm formation ability between microorganisms - Meng-Xin Hu; Fei He; Cheng-Kai Tu; Zhe-Xin Chen; Hui Teng; Xin Shao; Ge-Rui Ren; Ya-Xin Guo (Food Bioscience, 2023)

An investigation into the modal effect mechanism of multi-mode coupled flutter with modality-driven method - Jinbo Zhu; Yongxin Yang; Haojun Xu; Jinjie Zhang; Rushen Su; Yaojun Ge; Rui Zhou; Yizhe Lan (Engineering Structures, 2023)

A personalized regression model for predicting thermal sensation based on local skin temperature in moderate summer conditions - Yun Qi; Rui Wang; Chaoyi Zhao; Chao Ding; Chenqiu Du; Jiazheng Zhang; Xuan Zhang; Xinchang Chen; Mingjie Zhang; Qingfeng Bie; Meng Ge (Energy and Buildings, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Assessing the role and driving mechanisms of the green financial reform on urban energy consumption and pollution emissions: a policy evaluation from the generalized synthetic control method - Xiulu Huang; Rui Zhu; Xiaoxu Wu; Pengfei Ge (Environmental Science and Pollution Research, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Distribution of mudsnail Bullacta caurina along smooth cordgrass Spartina alterniflora invasion stages on a coast of the Yellow Sea, China - Li Yang; Jingyi Shi; Rui Pan; Ruiping Yang; Hongshan Li; Shuang Wang; Baoming Ge (Marine Environmental Research, 2023)

In vitro starch digestibility of maize flour and maize extruded noodles based on different particle-size effects - Rui Ge; Xiaojie Qian; Binghua Sun; Sen Ma; Xiaoxi Wang (Journal of Cereal Science, 2023)

Camel milk peptides alleviate hyperglycemia by regulating gut microbiota and metabolites in type 2 diabetic mice - Yongjin Zhang; Ju Wang; Wupeng Ge; Yuxuan Song; Rui He; Zhi Wang; Lili Zhao (Food Research International, 2023)

Quantitative proteomics analysis on the meat quality of processed pale, soft, and exudative (PSE)-like broiler pectoralis major by different heating methods - Tianyi Yang; Yamin Yang; Peng Zhang; Weitao Li; Qingfeng Ge; Hai Yu; Mangang Wu; Lidong Xing; Zhiyu Qian; Fan Gao; Rui Liu (Food Chemistry, 2023)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

Highly permeable PA@GO loose nanofiltration membranes enabled by hierarchical transport channels for efficient dye removal - Xia Zhan; Rui Ge; Teng Huo; Juan Lu; Jiding Li (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Using Ribonucleoprotein-based CRISPR/Cas9 to Edit Single Nucleotide on Human Induced Pluripotent Stem Cells to Model Type 3 Long QT Syndrome (SCN5A±) - Ning Ge; Min Liu; Rui Li; Nicholas M. Allen; Joseph Galvin; Sanbing Shen; Timothy O’Brien; Terence W. Prendiville (Stem Cell Reviews and Reports, 2023)
Human induced pluripotent stem cells (hiPSCs) have been widely used in cardiac disease modelling, drug discovery, and regenerative medicine as they can be differentiated into patient-specific cardiomyocytes. Long QT syndrome type 3 (LQT3) is one of the more malignant congenital long QT syndrome (LQTS) variants with an SCN5A gain-of-function effect on the gated sodium channel. Moreover, the predominant pathogenic variants in LQTS genes are single nucleotide substitutions (missense) and small insertion/deletions (INDEL). CRISPR/Cas9 genome editing has been utilised to create isogenic hiPSCs to control for an identical genetic background and to isolate the pathogenicity of a single nucleotide change. In this study, we described an optimized and rapid protocol to introduce a heterozygous LQT3-specific variant into healthy control hiPSCs using ribonucleoprotein (RNP) and single-stranded oligonucleotide (ssODN). Based on this protocol, we successfully screened hiPSCs carrying a heterozygous LQT3 pathogenic variant ( SCN5A ± ) with high efficiency (6 out of 69) and confirmed no off-target effect, normal karyotype, high alkaline phosphatase activity, unaffected pluripotency, and in vitro embryonic body formation capacity within 2 weeks. In addition, we also provide protocols to robustly differentiate hiPSCs into cardiomyocytes and evaluate the electrophysiological characteristics using Multi-electrode Array. This protocol is also applicable to introduce and/or correct other disease-specific variants into hiPSCs for future pharmacological screening and gene therapeutic development. Graphical Abstract

Transport model simulation prediction and environmental risk assessment of pyrethroid insecticides in urban artificial lakes caused by rainfall: A case study of Cloud Mountain Park in subhumid climate zone - Siyao Liu; Xuanying Li; Rui Ding; Yuwen Pan; Xiaoyu Ge; Weifang Ma (Journal of Environmental Management, 2023)

Comprehensive investigation of milk oligosaccharides in different mammalian species and the effect of breed and lactation period on sheep milk oligosaccharides - Haiyan Wang; Minghui Zhang; Yucui Huo; Xiuxiu Cui; Rui He; Bei Han; Zhongfu Wang; Yuxuan Song; Xin Lv; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Experimental features of emissions and fuel consumption in a car-following platoon - Shirui Zhou; Junfang Tian; Ying-En Ge; Shaowei Yu; Rui Jiang (Transportation Research Part D: Transport and Environment, 2023)

Ferulic acid enhanced resistance against blue mold of Malus domestica by regulating reactive oxygen species and phenylpropanoid metabolism - Mi Guo; Canying Li; Rui Huang; Linhong Qu; Jiaxin Liu; Chenyang Zhang; Yonghong Ge (Postharvest Biology and Technology, 2023)

A new insight into the polar lipid composition in mature breast milk and ewe milk with comparative lipidomics analysis - Shuangshuang Wang; Yuxuan Song; Rui He; Guanli Du; Lei Zhang; Bangjun Zhang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Constructing dendrite suppressing mixed sulfide solid electrolyte for high-rate lithium metal batteries - Zeyu Ge; Nanshan Chen; Rui Wang; Rui Ma; Bo Fan; David Le coq; Xianghua Zhang; Hongli Ma; Bai Xue (Chemical Engineering Journal, 2023)

Duox mediated ROS production inhibited WSSV replication in Eriocheir sinensis under short-term nitrite stress - Rui Jia; Xiaoling Dai; Yanfang Li; Xintong Yang; Xiuwen Min; Derun Quan; Peng Liu; Xin Huang; Jiachun Ge; Qian Ren (Aquatic Toxicology, 2023)

Compound and successive events of extreme precipitation and extreme runoff under heatwaves based on CMIP6 models - Peng Sun; Yifan Zou; Rui Yao; Zice Ma; Yaojin Bian; Chenhao Ge; Yinfeng Lv (Science of The Total Environment, 2023)

Tracing magnesium flows in China: A dynamic material flow analysis - Tianjiao Guo; Yong Geng; Xiaoqian Song; Xue Rui; Zewen Ge (Resources Policy, 2023)

Metabolism of hydrogen peroxide by Lactobacillus plantarum NJAU-01: A proteomics study - Lei Chen; Rui Liu; Suyun Li; Mangang Wu; Hai Yu; Qingfeng Ge (Food Microbiology, 2023)

Rapid identification of high and low cadmium (Cd) accumulating rice cultivars using machine learning models with molecular markers and soil Cd levels as input data - Zhong Tang; Ting-Ting You; Ya-Fang Li; Zhi-Xian Tang; Miao-Qing Bao; Ge Dong; Zhong-Rui Xu; Peng Wang; Fang-Jie Zhao (Environmental Pollution, 2023)

Characteristics prediction of hydrothermal biochar using data enhanced interpretable machine learning - Chao Chen; Zhi Wang; Yadong Ge; Rui Liang; Donghao Hou; Junyu Tao; Beibei Yan; Wandong Zheng; Rositsa Velichkova; Guanyi Chen (Bioresource Technology, 2023)

Insights into the bacterial and archaeal population dynamics in the deep-sea hydrothermal sediments exposed to lights with different wavelengths - Ge Liu; Yeqi Shan; Rui Liu; Chaomin Sun (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Methodological and reporting quality evaluation of Buyang Huanwu decoction for experimental cerebral ischemia–reperfusion injury: a systematic review - Xiangyu Chen; Tong Yang; Yanan Luo; Zhitao Feng; Rui Fang; Jinwen Ge; Zhigang Mei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Buyang Huanwu decoction, a classic traditional Chinese prescription, has been used to prevent and treat stroke for hundreds of years. An increasing number of the laboratory research on Buyang Huanwu decoction used in treating cerebral ischemia–reperfusion injury have been published recently. However, the problem of methodological and reporting quality of some studies is lack of assessment. This study aims to evaluate the methodological and reporting quality of the research on Buyang Huanwu decoction against experimental cerebral ischemia–reperfusion injury. A comprehensive search on six databases was performed. Two researchers independently screened the literature considering the eligibility criteria. Methodological and reporting quality of the included studies were evaluated by the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) risk-of-bias tool and Animal Research: Reporting of In Vivo Experiments (ARRIVE) guideline. Forty-five studies met the inclusion criteria. No study achieved a decent overall rating in using the SYRCLE tool (percentage of items with “low risk” ≥ 50%). Of the 22 items on the SYRCLE tool, only 7 items (31.82%) were rated as “low risk” in more than 50% of the included studies. Of the 39 items of ARRIVE guideline, 14 (35.9%) items were rated as “yes” in more than 50% of the included studies. The methodological and reporting quality of Buyang Huanwu decoction for experimental cerebral ischemia–reperfusion injury was substandard, which needed to be further improved. The limitations should be addressed when planning similar studies in the future. Additionally, these findings provided evidence-based guidance for future preclinical studies evaluating the efficacy of Buyang Huanwu decoction in the treatment of cerebral ischemia–reperfusion injury.

Role of moveable guide vane with various configurations in controlling the vortex-induced vibration of twin-box girder suspension bridges: An experimental investigation - Rui Zhou; Peng Lu; Xiaodong Gao; Yaojun Ge; Yongxin Yang; Lihai Zhang (Engineering Structures, 2023)

Full genome sequence of a novel iflavirus from the aster leafhopper Macrosteles fascifrons - Jiajing Xiao; Kai Zhu; Rui Ma; Chunmin Zhang; Keliang Lv; Danfeng Ge; Renyi Liu (Virus Genes, 2023)

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

2-hydroxy-3-phenylpropanoic acid suppressed the growth of Alternaria alternata through damaging cell membrane integrity and modulating reactive oxygen species metabolism - Jiaxin Liu; Canying Li; Chenyang Zhang; Rui Huang; Linhong Qu; Yonghong Ge (Fungal Biology, 2023)

Influence of different thermal treatment methods on the processing qualities of sesame seeds and cold-pressed oil - Ying Huang; Changsheng Liu; Zhengfa Ge; Fenghong Huang; Hu Tang; Qi Zhou; Rui Liu; Jiazhang Huang; Chang Zheng (Food Chemistry, 2023)

Case-driven assessment of power grid emergency response capability considering typhoon disaster scenario diversity - Zhao-ge Liu; Xiang-yang Li; Dilawar Khan Durrani; Rui-jin Zhang (Journal of Cleaner Production, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

Simulation of integrated anaerobic digestion-gasification systems using machine learning models - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Rui Liang; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Beibei Yan; Guanyi Chen (Bioresource Technology, 2023)

Synthesis and influencing factors of high-performance concrete based on copper tailings for efficient solidification of heavy metals - Ruosong Xie; Rui Ge; Zhishuncheng Li; Guangfei Qu; Yingjie Zhang; Youxiao Xu; Yingda Zeng; Ziying Li (Journal of Environmental Management, 2023)

Identification of high iron–chelating peptides with unusual antioxidant effect from sea cucumbers and the possible binding mode - Chaozhong Fan; Xiaofan Ge; Junyu Hao; Tao Wu; Rui Liu; Wenjie Sui; Jieting Geng; Min Zhang (Food Chemistry, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Oxidative stress and inflammation caused by 1-tetradecyl-3-methylimidazolium tetrafluoroborate in rat livers - Huafei Yuan; Feng Xu; Xingxing Tian; Haiyan Wei; Rui Zhang; Yueyue Ge; Hongmei Xu (Environmental Science and Pollution Research, 2022)

Nitrogen occurrence forms and bacterial community in sediment influenced by Bellamya purificata bioturbation - Yiyun Zhang; Yiran Hou; Rui Jia; Bing Li; Jian Zhu; Xianping Ge (Frontiers in Marine Science, 2022)
Endogenous water pollution and excessive nitrogen in ponds have always been prominent problems threatening aquaculture. To solve this problem, a 70-day indoor simulation experiment was conducted. The snail Bellamya purificata was stocked at four different densities: 0, 15, 30, and 60 individuals/tank, represented as CON (control), LD (low density), MD (medium density), and HD (high density), respectively, to investigate the effects of B. purificata on the nitrogen occurrence forms and bacterial communities in the sediment. At the end of the experiment, the nitrate concentration was significantly higher, while the total nitrogen content was significantly lower in the MD group than in the other three groups. Ammonia monooxygenase activity was significantly lower in the CON group than in the other three groups, and hydroxylamine oxidase activity was significantly higher in the HD group than in the other three groups. The CON and MD groups showed the highest and lowest values in nitrate reductase activity, respectively. The hydroxylamine reductase activity decreased significantly with increasing density. Through 16S ribosomal RNA (rRNA) high-throughput sequencing, significantly affected bacterial communities by B. purificata were found. Alpha diversity results showed that, a significantly lower Shannon index was observed in the MD group than in the other three groups. The LD and MD groups showed the highest and lowest Chao1 index values, respectively. Phyla Nitrospinae and family Nitrosomonadaceae were significantly enriched in the HD and MD groups, respectively. Redundancy analysis (RDA) indicated a significant correlation between differential bacterial taxa and TN content. Predicted functional analysis based on FAPROTAX (Functional annotation of prokaryotic taxa) database showed that functional groups aerobic ammonia oxidation and aerobic nitrite oxidation were significantly enriched in the MD group. Overall, B. purificata significantly altered the bacterial community composition, increased hydroxylamine oxidase and ammonia monooxygenase activities, enhanced the bacterial nitrification process, and promoted the transformation of total nitrogen to nitrate. Moreover, B. purificata stocked at 30 and 60 individuals/tank appeared to have a significant promotion effect on the bacterial community and nitrogen occurrence forms in the sediment. Hence, co-culturing B. purificata may be a feasible and effective ecological restoration method to alleviate excess nitrogen and reduce water eutrophication.

Evolutions of upwelling and terrestrial organic matter input in the inner shelf of the East China Sea in the last millennium revealed by long-chain alkyl diols proxies - Chuanhui Song; Tianxiang Dang; Ting Zhang; Tiantian Ge; Rong Xiang; Lei Xing; Rui Bao; Yang Zhou; Rui Xiao; Baojin Wu (Frontiers in Marine Science, 2022)
Long-chain alkyl diols (LCDs) can be used as organic geochemical proxies for paleoceanographic change, especially in marginal sea areas where large volumes of sediments are deposited rapidly and continuously. However, little is known about the applicability and response on a millennium scale in relation with existing records in those sediments. We reconstruct changes in upwelling and terrestrial organic matter (OM) input in core sediments from the Zhejiang Fujian coastal station (T08) and Yangtze River Estuary station (T06) in the inner shelf of the East China Sea (ECS) over the last millennium, using the LCD based proxies: diol index 2 (DI-2), and FC 32 1,15-diol. Our results show that DI-2 values ([(C 28 +C 30 )1,14-diols]/([(C 28 +C 30 )1,13-diols]+[(C 28 +C 30 )1,14-diols])) at T08 decrease significantly during 600–400 yr BP but increase gradually after 400 yr BP. The FC 32 1,15-diol proxy ([C 32 1,15-diol]×100/([(C 28 +C 30 )1,13-diols]+[(C 30 +C 32 )1,15-diols])) at T06 shows marked fluctuations during 1000–800 yr BP, followed by a significant decline during 800–500 yr BP but a subsequent increase from 500 to 300 yr BP. We find that variations in DI-2 values are broadly consistent with changes in the strength of the East Asian Summer Monsoon (EASM) and the Kuroshio Current and are likely linked to changes in the frequency and intensity of the El Niño-Southern Oscillation (ENSO). The increased strength of the EASM causes greater offshore movement of the upper layer of seawater, which in turn triggers upwelling of bottom waters formed by Kuroshio subsurface waters. We find that variations in FC 32 1,15-diol proxy are controlled mainly by the East Asian Winter Monsoon (EAWM) and the Yangtze River discharge. By increasing the strength of the EAWM, southward transportation of material deposited in the estuary of the Yangtze River by the ECS coastal currents is promoted. In addition, we synthesize records of other organic geochemical indicators nearby core sediments in the ECS; these records emphasize the importance of reconstructing the evolutionary history of upwelling and subdividing the relative inputs of terrestrial OM. Our study provides a new means for reconstructing the evolution of upwelling and terrestrial OM input in the inner shelf of the ECS over the last millennium.

Triphenylpyrazoline ketone chlorophenols as potential candidate compounds against Parkinson’s disease: design, synthesis, and biological evaluation - Ning Ning Cheng; Le Hua Zhang; Rui Ge; Xiu E. Feng; Qing Shan Li (Medicinal Chemistry Research, 2022)

Reduction the contamination of patulin during the brewing of apple cider and its characteristics - Zhouli Wang; Leran Wang; Qiaoying Ming; Tianli Yue; Qian Ge; Yahong Yuan; Zhenpeng Gao; Rui Cai (Food Additives & Contaminants: Part A, 2022)

Polar Sea Ice Identification and Classification Based on HY-2A/SCAT Data - Rui Xu; Chaofang Zhao; Xiaochun Zhai; Ke Zhao; Jichang Shen; Ge Chen (Journal of Ocean University of China, 2022)

QTL mapping and candidate gene prediction for fiber yield and quality traits in a high-generation cotton chromosome substitution line with Gossypium barbadense segments - Quanwei Lu; Pengtao Li; Rui Yang; Xianghui Xiao; Ziyin Li; Qiuyu Wu; Juwu Gong; Qun Ge; Aiying Liu; Shengli Du; Jundi Wang; Yuzhen Shi; et al. (Molecular Genetics and Genomics, 2022)

Pseudonocardia humida sp. nov., an Actinomycete Isolated from Mangrove Soil Showing Distinct Distribution Pattern of Biosynthetic Gene Clusters - Zhen-Yu Zan; Xian-Feng Ge; Rui-Rui Huang; Wen-Zheng Liu (Current Microbiology, 2022)

GIS-based spatial prediction of landslide using road factors and random forest for Sichuan-Tibet Highway - Cheng-ming Ye; Rui-long Wei; Yong-gang Ge; Yao Li; José Marcato Junior; Jonathan Li (Journal of Mountain Science, 2022)

Seasonal variation of oxidative potential of water-soluble components in PM2.5 and PM1 in the Yangtze River Delta, China - Zhirao Li; Dongyang Nie; Mindong Chen; Pengxiang Ge; Zhengjiang Liu; Xiaoyun Ma; Xinlei Ge; Rui Gu (Air Quality, Atmosphere & Health, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Biotreatment of Cr(VI) and pyrene combined water pollution by loofa-immobilized bacteria - Xinjiao Dong; Yaru Li; Rui Zhu; Chuanhua Wang; Shimei Ge (Environmental Science and Pollution Research, 2021)

Maribellus comscasis sp. nov., a novel deep‐sea Bacteroidetes bacterium, possessing a prominent capability of degrading cellulose - Rikuan Zheng; Ruining Cai; Rui Liu; Ge Liu; Chaomin Sun (Environmental Microbiology, 2021)
Summary Bacteroidetes are thought to be specialized for the degradation of algae‐derived ocean polysaccharides. Here, we show that Bacteroidetes are the predominant phylum in deep‐sea sediments and possess more genes associated with polysaccharides degradation than other bacteria. We have isolated a novel Bacteroidetes species from the deep‐sea sediments by using a special polysaccharide containing medium, Maribellus comscasis WC007, which possesses 82 putative polysaccharide utilization loci (PULs) containing 374 glycoside hydrolases and 82 SusC/D pairs (Sus indicates s tarch u tilization s ystem; SusC represents the actual TonB‐dependent transporter, and SusD is an associated substrate‐binding outer membrane lipoprotein) together with 58 sigma/antisigma factors. Through an in‐depth analysis of these PULs, strain WC007 can efficiently degrade numerous different polysaccharides including cellulose, pectin, fucoidan, mannan, xylan and starch, which are verified by growth assays. Notably, we find that cellulose has the most significant growth‐promoting effect on M . comscasis WC007. And based on scanning electron microscope observation, transcriptomics and metabolomics, we further report on the underlying mechanisms of cellulose degradation and utilization, as well as potential contributions to the carbon cycle. Overall, our results suggest that Bacteroidetes may play key roles in the carbon cycle, likely due to their high abundance and prominent polysaccharide degradation capabilities.

Growth promotion of a deep‐sea bacterium by sensing infrared light through a bacteriophytochrome photoreceptor - Ge Liu; Yeqi Shan; Rikuan Zheng; Rui Liu; Chaomin Sun (Environmental Microbiology, 2021)
Summary Photoreceptors are found in all kingdoms of life and bacteriophytochromes (Bphps) are the most abundant photo‐sensing receptors in bacteria. Interestingly, BphPs have been linked to some bacterial physiological responses, yet most of the biological processes they regulate are still elusive, especially in non‐photosynthetic bacteria. Here, we show that a bacteriophytochrome (CmoBphp) from a deep‐sea bacterium Croceicoccus marinus OT19 perceives infrared light (wavelength at 940 nm) and transduces photo‐sensing signals to a downstream intracellular transduction cascade for better growth. We discover that the infrared light‐mediated growth promotion of C. marinus OT19 is attributed partly to the enhancement of pyruvate and propanoate metabolism. Further study suggests that CmoBphp plays a crucial role in integrating infrared light with intracellular signalling to control the bacterial growth and metabolism. This is the first report that deep‐sea non‐photosynthetic bacteria can sense infrared light to control growth through a bacteriophytochrome photoreceptor, thus providing new understandings towards light energy utilization by microorganisms.

Calcium protects bacteria against cadmium stress via reducing nitric oxide production and increasing iron acquisition - Zuodong Wu; Rikuan Zheng; Ge Liu; Rui Liu; Shimei Wu; Chaomin Sun (Environmental Microbiology, 2021)
Summary Cadmium (Cd) is a common toxic heavy metal in the environment, and bacteria have evolved different strategies against Cd‐toxicity. Here, we found that marine bacterium Bacillus sp. 98 could significantly alleviate Cd‐toxicity by recruiting calcium (Ca) for reducing excessive intracellular nitric oxide (NO) and enhancing iron acquisition. To investigate the underlying mechanisms, mass spectrometry‐based proteomic analysis was applied to Bacillus sp. 98 after treated with Cd supplemented with or without Ca. Compared with bacterial cells treated with Cd only, the proteomic results showed that the expression level of NO synthase was markedly down‐regulated, while the expression levels of NO dioxygenase, which is responsible for converting NO to nitrate, and proteins associated with iron uptake were profoundly enhanced when Ca was supplemented. Consistently, bacterial intracellular NO amount was dramatically increased after Bacillus sp. 98 was treated with Cd, and reversed to a normal level when Ca or iron was supplemented. Notably, Ca also protected bacteria against stresses from other heavy metals including Cu, Cr, Mn, Ni and Zn, and this self‐protection strategy was adopted as well in zebrafish, which encourages us to develop Ca‐associated products against heavy metals toxicity in the future.

3D DEM analysis on tractive trafficability of a lunar rover wheel with bionic wheel lugs - Hao Pang; Rui Zhang; Ping Ge; Fang Liu; Chengjin Wang; Wenchao Dong; Tao Li; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Contrasting pathways of carbon sequestration in paddy and upland soils - Xiangbi Chen; Yajun Hu; Yinhang Xia; Shengmeng Zheng; Chong Ma; Yichao Rui; Hongbo He; Daoyou Huang; Zhenhua Zhang; Tida Ge; Jinshui Wu; Georg Guggenberger; et al. (Global Change Biology, 2021)
Paddy soils make up the largest anthropogenic wetlands on earth, and are characterized by a prominent potential for organic carbon (C) sequestration. By quantifying the plant‐ and microbial‐derived C in soils across four climate zones, we identified that organic C accrual is achieved via contrasting pathways in paddy and upland soils. Paddies are 39%–127% more efficient in soil organic C (SOC) sequestration than their adjacent upland counterparts, with greater differences in warmer than cooler climates. Upland soils are more replenished by microbial‐derived C, whereas paddy soils are enriched with a greater proportion of plant‐derived C, because of the retarded microbial decomposition under anaerobic conditions induced by the flooding of paddies. Under both land‐use types, the maximal contribution of plant residues to SOC is at intermediate mean annual temperature (15–20°C), neutral soil (pH~7.3), and low clay/sand ratio. By contrast, high temperature (~24°C), low soil pH (~5), and large clay/sand ratio are favorable for strengthening the contribution of microbial necromass. The greater contribution of microbial necromass to SOC in waterlogged paddies in warmer climates is likely due to the fast anabolism from bacteria, whereas fungi are unlikely to be involved as they are aerobic. In the scenario of land‐use conversion from paddy to upland, a total of 504 Tg C may be lost as CO 2 from paddy soils (0–15 cm) solely in eastern China, with 90% released from the less protected plant‐derived C. Hence, preserving paddy systems and other anthropogenic wetlands and increasing their C storage through sustainable management are critical for maintaining global soil C stock and mitigating climate change.

Integrated analysis of miRNA and mRNA transcriptomic reveals antler growth regulatory network - Boyin Jia; Linlin Zhang; Yifan Zhang; Chenxia Ge; Fuhe Yang; Rui Du; Hengxing Ba (Molecular Genetics and Genomics, 2021)

Farrerol maintains the contractile phenotype of VSMCs via inactivating the extracellular signal-regulated protein kinase 1/2 and p38 mitogen-activated protein kinase signaling - Enli Liu; Shasha Shi; Jie Li; Rui Ge; Taigang Liang; Qingshan Li (Molecular and Cellular Biochemistry, 2020)

The cyclic lipopeptides suppress the motility of Vibrio alginolyticus via targeting the Na + ‐driven flagellar motor component MotX - Rui Liu; Rikuan Zheng; Ge Liu; Chaomin Sun (Environmental Microbiology, 2020)
Summary In our previous study, we found that pumilacidin‐like cyclic lipopeptides (CLPs) derived from marine bacterium Bacillus sp. strain 176 significantly suppressed the mobile capability and virulence of Vibrio alginolyticus . Here, to further disclose the mechanism of CLPs inhibiting the motility of V . alginolyticus , we first applied transcriptomic analysis to V . alginolyticus treated with or without CLPs. The transcriptomic results showed that the expression of several important components of the Na + ‐driven flagellar motor closely related to bacterial motility were markedly suppressed, suggesting that the structure and function of Na + ‐driven flagellar motor might be disabled by CLPs. The transcriptomic data were further analysed by the protein–protein interaction network, and the results supported that MotX, one of the essential components of Na + ‐driven flagellar motor was most likely the action target of CLPs. In combination of gene knockout, electrophoretic mobility shift assay and immunoblotting techniques, CLPs were demonstrated to affect the rotation of flagella of Vibrio alginolyticus via direct interacting with the Na + ‐driven flagellar motor component MotX, which eventually inhibited the bacterial motility. Interestingly, homologues of MotX were found broadly distributed and highly conserved in different pathogenic species, which extends the application range of CLPs as an antibacterial drug targeting bacterial motility in many pathogens.

Gradation affects basic mechanical characteristics of Chinese calcareous sand as airport subgrade of reefs - Shen Yang; Xue Shen; Hanlong Liu; Huayang Ge; Xiaoxi Rui (Marine Georesources & Geotechnology, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Disruption of the lactate dehydrogenase and acetate kinase genes in Klebsiella pneumoniae HD79 to enhance 2,3-butanediol production, and related transcriptomics analysis - Jingping Ge; Jiawang Wang; Guangbin Ye; Shanshan Sun; Rui Guo; Gang Song; Wenxiang Ping (Biotechnology Letters, 2020)

Systematic Identification and Comparative Analysis of Human Cartilage-Derived Self-peptides Presented Differently by Ankylosing Spondylitis (AS)-Associated HLA-B*27:05 and Non-AS-associated HLA-B*27:09 - Chang Ge; Wenzhi Zhang; Rui He; Haiping Cai (International Journal of Peptide Research and Therapeutics, 2020)

Antioxidative and Probiotic Activities of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China - Yunjia Shi; Xingyang Cui; Shanshan Gu; Xin Yan; Rui Li; Shuang Xia; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2019)

A transcriptome analysis uncovers Panax notoginseng resistance to Fusarium solani induced by methyl jasmonate - Diqiu Liu; Qin Zhao; Xiuming Cui; Rui Chen; Xin Li; Bingling Qiu; Feng Ge (Genes & Genomics, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

Fluorophenols bearing nitrogenated heterocycle moieties, a class of novel Keap1-Nrf2 protein-protein interaction inhibitors: synthesis, antioxidant stress screening and molecular docking - Xiu E Feng; De Peng Kong; Shu Rong Ban; Rui Ge; Qing Shan Li (Medicinal Chemistry Research, 2019)

Overexpression of BcbZIP134 negatively regulates the biosynthesis of saikosaponins - Jiao Xu; Su-Rui Wu; Yan-Hong Xu; Zhan-Yu Ge; Chun Sui; Jian-He Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Antioxidant defense against rust infection in the leaf tissue of Malus crabapple - Yudan Duan; Suxiao Hao; Rui Luo; Yanfen Lu; Ge Li; Jie Zhang; Ji Tian; Yuncong Yao (Acta Physiologiae Plantarum, 2019)

Genomic characterization and pathogenicity of porcine deltacoronavirus strain CHN-HG-2017 from China - Meng-Jia Zhang; De-Jian Liu; Xiao-Li Liu; Xing-Yi Ge; Anan Jongkaewwattana; Qi-Gai He; Rui Luo (Archives of Virology, 2019)

A new persistent luminescent composite for tracing toxic air particulate matter - Pinghui Ge; Yanjie Liang; Yuan Cheng; Kangning Sun; Rui Liu (Environmental Chemistry Letters, 2018)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

Metatranscriptomics analysis of cyanobacterial aggregates during cyanobacterial bloom period in Lake Taihu, China - Zhenzhu Chen; Junyi Zhang; Rui Li; Fei Tian; Yanting Shen; Xueying Xie; Qinyu Ge; Zuhong Lu (Environmental Science and Pollution Research, 2018)

A Fluorescent Sensor of 3-Aminobenzeneboronic Acid Functionalized Hydrothermal Carbon Spheres for Facility Detection of L-tryptophan - Rui Zhang; Li-Xia Wang; Yun-Di Zhang; Chun-Hua Ge; Jia-Ping Wang; Ying Zhang; Xiang-Dong Zhang (Journal of Fluorescence, 2018)

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

Microbial profiles of a drinking water resource based on different 16S rRNA V regions during a heavy cyanobacterial bloom in Lake Taihu, China - Junyi Zhang; Congming Zhu; Rui Guan; Zhipeng Xiong; Wen Zhang; Junzhe Shi; Yi Sheng; Bingchuan Zhu; Jing Tu; Qinyu Ge; Ting Chen; Zuhong Lu (Environmental Science and Pollution Research, 2017)

Functional characterization of a pathogenesis-related protein family 10 gene, LrPR10-5, from Lilium regale Wilson - Rui Chen; Hua He; Ye Yang; Yuan Qu; Feng Ge; Diqiu Liu (Australasian Plant Pathology, 2017)

Biological traits yield divergent phylogeographical patterns between two aphids living on the same host plants - Fang Fang; Jing Chen; Li‐Yun Jiang; Rui Chen; Ge‐Xia Qiao (Journal of Biogeography, 2017)
Aim Animals' phylogeographical patterns are frequently explained by Pleistocene glacial fluctuations and topographical environments. However, species‐specific biological traits are thought to have profound impacts on distribution patterns, particularly in aphids. We hypothesize that the phylogeographical patterns and/or population dynamics of two sympatric aphids may be different due to their different reproductive modes and feeding sites, even though they share the same hosts and environmental conditions. Location China. Methods We explored our hypothesis in Chaitophorus saliniger and Tuberolachnus salignus , two aphids that share the same host plants (genus Salix ) but differ biologically. Chaitophorus saliniger is characterized by alternating sexual and asexual reproduction and only feeds on willow leaves, whereas T. salignus has obligate asexual reproduction and feeds on trunks and branches. The genetic diversity, population structure and demographic history of the aphids were analysed based on both mitochondrial DNA (cytochrome c oxidase subunit I and cytochrome b ) and nuclear DNA (translation elongation factor 1 alpha). Ecological niche models ( ENM s) were used to explore historical changes in distribution. The chief environmental variables that discriminate the different haplogroups were identified through multivariate statistical analysis. Results There were striking differences in the phylogeographical patterns between the species. The sexual C. saliniger exhibited higher genetic diversity and population variations than the asexual T. salignus . According to genetic analyses and ENM s, both species experienced glacial contraction and post‐glacial expansion. Multivariate statistical analysis revealed that the climatic differences between the divergent haplogroups were explained by principal components mainly loaded with temperature and elevation. Main conclusions Our results suggest that species‐specific biological traits and historical climate fluctuations have both shaped the current phylogeographical patterns of both aphid species. Their distinct genetic diversity and population structures highlight the importance of intrinsic biological features in driving phylogeographical patterns.

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

Multiple Responsive Polymer-Peptide Bioconjugate - Xi-Rui Zhou; Rui Ge; Guofeng Li; Long Chen; Tianwei Tan; Xing Wang; Shi-Zhong Luo (International Journal of Peptide Research and Therapeutics, 2015)

Mutations in human IFT140 cause non-syndromic retinal degeneration - Mingchu Xu; Lizhu Yang; Feng Wang; Huajin Li; Xia Wang; Weichen Wang; Zhongqi Ge; Keqing Wang; Li Zhao; Hui Li; Yumei Li; Ruifang Sui; et al. (Human Genetics, 2015)

Suppression of spring rain by surface greening over North China Plain - Xuezhen Zhang; Qiuhong Tang; Jingyun Zheng; Quansheng Ge; Rui Mao (International Journal of Climatology, 2015)
Surface greenness and rainfall in spring have changed from the 1980s to 1990s over the North China Plain (NCP). The greenness changes are characterized by large increase in north and little in south with an obvious greening zone from the centre of the NCP to the northeast. The rainfall change has a similar spatial pattern with reversed sign. The correlation between changes in greenness and rainfall is significant and the correlation ( r = −0.71, p

Stromal cell-derived factor 1 (SDF-1) accelerated skin wound healing by promoting the migration and proliferation of epidermal stem cells - Rui Guo; Linlin Chai; Liang Chen; Wenguang Chen; Liangpeng Ge; Xiaoge Li; Hongli Li; Shirong Li; Chuan Cao (In Vitro Cellular & Developmental Biology - Animal, 2015)

Village network centrality in rural tourism destination: A case from Yesanpo tourism area, China - Rui-ying Zhang; Jian-chao Xi; Shou-kun Wang; Xin-ge Wang; Quan-sheng Ge (Journal of Mountain Science, 2015)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

A Clinical Study of Patients with Coronary Heart Disease Complicated with Hypertriglyceridemic Waist Phenotype - Rui-feng Yang; Zhi Lin; Xiao-yong Liu; Ge Zhang (Cell Biochemistry and Biophysics, 2014)

Tumor Necrosis Factor (TNF)-alpha Promoter Polymorphisms in Ankylosing Spondylitis: Comment on the Article by Ji et al - Zhongwen Chen; Rui Ge (Cell Biochemistry and Biophysics, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

An Endophytic Sanguinarine-Producing Fungus from Macleaya cordata, Fusarium proliferatum BLH51 - Xue-Jun Wang; Chang-Li Min; Mei Ge; Rui-Hua Zuo (Current Microbiology, 2014)

A new algorithm for tight integration of real-time GPS and strong-motion records, demonstrated on simulated, experimental, and real seismic data - Rui Tu; Maorong Ge; Rongjiang Wang; Thomas R. Walter (Journal of Seismology, 2014)

Sorption Behavior of Phosphate on an MSWI Bottom Slag and Sewage Sludge Co-sintered Adsorbent - Suyang Ge; Hui Zhang; Hai Ye; Houhu Zhang; Keqiang Zhao; Qinfang Sun; Rui Wu; Wenping Cao (Water, Air, & Soil Pollution, 2013)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Investigation on pretreatment of centrifugal mother liquid produced in the production of polyvinyl chloride by air-Fenton technique - Yingying Sun; Xiuyi Hua; Rui Ge; Aitong Guo; Zhiyong Guo; Deming Dong; Wentian Sun (Environmental Science and Pollution Research, 2013)

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study - Rui Ge; Faming Pan; Fangfang Liao; Guo Xia; Yang Mei; Beibei Shen; Tianchen Zhang; Jing Gao; Li Zhang; Zhenhua Duan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

No significant association between Fc receptor-like 3 gene polymorphisms and human leukocyte antigen-B27 positive ankylosing spondylitis in Han Chinese population - Guo Xia; Faming Pan; Fangfang Liao; Xiaowu Tang; Rui Ge; Yang Mei; Heping Pan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2010)

Effects of Neuregulin on Expression of MMP-9 and NSE in Brain of Ischemia/Reperfusion Rat - Qin Li; Rui Zhang; Yin-lin Ge; Yuan-wu Mei; Yun-liang Guo (Journal of Molecular Neuroscience, 2009)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Interaction of DNA-binding proteins with the 5′-flanking region of a cytokinin-responsive cucumber hydroxypyruvate reductase gene - Ge Jin; Maria C. Davey; John R. Ertl; Rui Chen; Zhu-tian Yu; Steven G. Daniel; Wayne M. Becker; Chong-maw Chen (Plant Molecular Biology, 1998)